Dietary supplementation with Agaricus blazei murill extract prevents diet‐induced obesity and insulin resistance in rats1. (17th April 2013) - Vincent, Mylène; Philippe, Erwann; Everard, Amandine; Kassis, Nadim; Rouch, Claude; Denom, Jessica; Takeda, Yorihiko; Uchiyama, Shoji; Delzenne, Nathalie M.; Cani, Patrice D.; Migrenne, Stéphanie; Magnan, Christophe
Abstract Objective: Dietary supplement may potentially help to fight obesity and other metabolic disorders such as insulin‐resistance and low‐grade inflammation. The present study aimed to test whether supplementation with Agaricus blazei murill (ABM) extract could have an effect on diet‐induced obesity in rats. Design and Methods: Wistar rats were fed with control diet (CD) or high‐fat diet (HF) and either with or without supplemented ABM for 20 weeks. Results: HF diet‐induced body weight gain and increased fat mass compared to CD. In addition HF‐fed rats developed hyperleptinemia and insulinemia as well as insulin resistance and glucose intolerance. In HF‐fed rats, visceral adipose tissue also expressed biomarkers of inflammation. ABM supplementation in HF rats had a protective effect against body weight gain and all study related disorders. This was not due to decreased food intake which remained significantly higher in HF rats whether supplemented with ABM or not compared to control. There was also no change in gut microbiota composition in HF supplemented with ABM. Interestingly, ABM supplementation induced an increase in both energy expenditure and locomotor activity which could partially explain its protective effect against diet‐induced obesity. In addition a decrease in pancreatic lipase activity is also observed in jejunum of ABM‐treated rats suggesting a decrease in lipid absorption. Conclusions: Taken together these data highlight a role for ABM to prevent body weight gain and related disorders in peripheral targets independently of effect in food intake in central nervous system.